Persistence of a Distinct Corynebacterium diphtheriae Clonal Group within Two Communities in the United States and Canada Where Diphtheria Is Endemic - Marston, Chung K. (American Society for Microbiology, 2001)
Molecular characterization of 53 U.S. and Canadian Corynebacterium diphtheriae isolates by multilocus enzyme electrophoresis, ribotyping, and random amplified polymorphic DNA showed that strains with distinct molecular subtypes have persisted in the United States and Canada for at least 25 years. These strains are endemic rather than imported from countries with current endemic or epidemic diphtheria.